Effect of harvesting dates on the yield and quality attributes of the wheat cultivars - Nagpal, Anmolpreet Singh; Kaur, Kawaljeet (Journal of Postharvest Technology, 2020)
Harvesting is the important parameter both for the researchers and the farmers. The harvesting of the crop should be done at the optimum time. The early, as well as the late harvest of the crop both, will lead to an irrecoverable loss in the yield of the crop. Many studies have been done on the harvesting of the wheat crop. It is the common practice in the case of wheat crop that the farmer will use the same seed again and again over the years, sometimes due non availability of resources the harvesting is delayed and to check the effect of harvesting dates an experiment was done in which the crop was harvested continuously for four days to find the effect of harvesting on the yield and its related attributes. Germination was less than the normal but was not having any significant difference. The germination percent of HD 3086 T1 (first harvesting) was 95.33% while T4 (Fourth harvesting) was 94.33%, whilst PBW 343 T1 (94.66%) and T4 (93.33%). The dry weight was showing best result for both varieties at first harvest HD30886 T1 (0.22) and PBW 343 T1 (0.15) as compare to the fourth harvest T4 (0.18) and PBW 343 T4 (0.11) respectively. The similar trend was followed for vigour index the highest vigour was of first harvest and lowest for the fourth harvest HD30886 T1 (20.89) and PBW 343 T1 (14.12) as compare to the fourth harvest T4 (17.34) and PBW 343 T4 (10.60).